2017
DOI: 10.1002/smi.2754
|View full text |Cite
|
Sign up to set email alerts
|

PTSD and PTG among Israeli mothers: Opposite facets of exposure to terrorism

Abstract: The aim of the this study was to test the association between posttraumatic stress disorder (PTSD), posttraumatic growth (PTG), and coping strategies among Israeli mothers with prolonged exposure to rocket missiles. One hundred fifty-two mothers, from the Western Negev region of Israel, took part in the study. Respondents were affected by prolonged exposure to missile attacks even when they themselves had not been hit or injured. A positive correlation was found between PTSD and PTG. Problem-focused coping was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
1
15
1
Order By: Relevance
“…We also found additional corroboration of the assumption that sense of fear depends on subjective inner feelings—not only actual exposure to threatening incidents (Silver, Holman, McIntosh, Poulin, & Gil-Rivas, 2002; Solomon & Lavi, 2005). This finding is also confirmed in mothers from Sderot and the Gaza envelope (Shechory-Bitton, 2013; Shechory-Bitton & Laufer, 2017), a residential area that has been exposed to missiles for years…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…We also found additional corroboration of the assumption that sense of fear depends on subjective inner feelings—not only actual exposure to threatening incidents (Silver, Holman, McIntosh, Poulin, & Gil-Rivas, 2002; Solomon & Lavi, 2005). This finding is also confirmed in mothers from Sderot and the Gaza envelope (Shechory-Bitton, 2013; Shechory-Bitton & Laufer, 2017), a residential area that has been exposed to missiles for years…”
Section: Discussionmentioning
confidence: 61%
“…Based on Solomon and Lavi’s (2005) Exposure to War and Terror Questionnaire (see also Shechory-Bitton, 2013; Shechory-Bitton & Laufer, 2017), 16 items on different types of trauma-related incidents were used to assess objective exposure to terror and security incidents (all the items are listed in Table 1). Objective exposure was scored as the total number of terror incidents to which the respondent had been exposed; scores ranged from 0 to 16, with higher scores indicating greater exposure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been confirmed that high levels of distress are the precondition of the PTG (Tedeschi & Calhoun, 2004). Researchers also concluded that post‐traumatic stress disorders (PTSD) is positively connected with PTG (Shechory Bitton & Laufer, 2017). In a word, patients with COPD are the ideal research objects of PTG given their frequent exposure to the exacerbation, high incidence rate, risk of negative emotions, and potential for positive changes.…”
Section: Introductionmentioning
confidence: 99%
“…PTG manifests in the acquisition of important valued resources, including greater appreciation of life, increased sense of personal strength, identification of new possibilities, positive spiritual change and improved interpersonal relationships, all of which are conducive to a more adaptive psychological functioning 10 ) . Although the relationship between PTSS and PTG remains unclear 26 ) , positive psychological changes following a trauma have been identified among a broad range of victims 27 , 28 , 29 ) . Thus, taken together, COR theory 16 , 17 ) and the post-traumatic stress literature suggest that: a) employees affected by PTSS might experience PTG; and b) such a positive transformation is contingent upon the possibility for the victims to reinvest their available energetic resources towards a cognitive reappraisal of the meaning attributed to the traumatic event.…”
Section: Introductionmentioning
confidence: 99%